Dignity, Autonomy, and Allocation of Scarce Medical Resources During COVID-19 - Kirchhoffer, David G. (J Bioeth Inq, 2020)
Ruth Macklin argued that dignity is nothing more than respect for persons or their autonomy. During the COVID-19 pandemic, difficult decisions are being made about the allocation of scarce resources. Respect for autonomy cannot justify rationing decisions. Justice can be invoked to justify rationing. However, this leaves an uncomfortable tension between the principles. Dignity is not a useless concept because it is able to account for why we respect autonomy and for why it can be legitimate to override autonomy in times of critical care resource shortages. Dignity affirms the worth of the human individual as a meaning-making embodied subject, who is always in relationship to others, the world, time, and transcendence, and who realizes their dignity through their moral behaviour. Such an understanding means people should be helped to make morally right decisions about their own treatment, which may include forgoing potentially beneficial treatment for the good of others. Respect for dignity does not require fulfilling the morally wrong choices of one who insists on treatment at the expense of others. Dignity also protects the discretion of clinicians to make decisions appropriate to their competence by prohibiting the application of broad-based criteria such as age.